PERKEMBANGAN KARIR GURU - Dewi, Asnita Putri; Rusdinal, Rusdinal (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
This research aimed at finding out the teacher?s career development of elementary school in Padang. This research was a descriptive study. The population were all teachers of elementary school in Padang North which consist of 238 people. The sample in this research was 78 people with a Slovin formula. The instrument of this research was questionnaire using Likert scale model which has proven validity and reliability. The results of this research showed that the average score of the teacher's career development of elementary school in Padang North was enough category.